Chlorine transformation during iron ore sintering co-processing of MSWI fly ash: Phase evolution, metal coupling, and risk-relevant environmental stability - Run Shi; Hao Wang; Congqi Zhang; Rongrong Lei; Hongzhi Ma; Yi Xing; Wei Su; Tingshuang Leng; Yulan Liang (Journal of Hazardous Materials, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Suppression effect and mechanism of expandable phosphorus-boron composite suppressant on Al dust explosion - Tianjiao Zhang; Xinrui Shi; Run Xia; Xingqiang Tian; Junjiang He (Journal of Cleaner Production, 2026)

Mapping the effectiveness of inter-regional industrial co-processing of municipal incineration fly ash: Evidence from the capital metropolitan area in China - Xinyi Zhang; Run Shi; Fan Fei; Zongguo Wen; Hongzhi Ma; Jiayue Zhang; Liping Zhang (Journal of Environmental Management, 2026)

Urban cooling effects of China’ s low-carbon city policy: Causal evidence from satellite-derived urban heat islands - Haoxiang Zhao; Jiawei Liu; Tingting Bai; Xiangbin Peng; Yuan Yuan; Run Shi; Yuanzheng Cui (Energy Policy, 2026)

VIIRS nighttime lights and geospatial constraints for monitoring commercial vitality and temporal hierarchy dynamics in Southeast Asia 2013–2024 - Run Shi; Yankai Liu; Song Liu; Xiangbin Peng; Bowen Song; Jianwei Gao; Fang Bian; Teng Zhong; Yuanzheng Cui (International Journal of Remote Sensing, 2026)

ClO₂-induced VBNC state in Enterococcus faecalis poses a health risk in drinking water systems - Ziyi Zhang; Shuai Cheng; Menghua Duan; Yihong Wang; Weipeng Xu; Yiming Lu; Hui Yang; Na Lv; Run Ma; Jiahui Guo; Chao Shi (Journal of Hazardous Materials, 2026)

Insights into the regulatory role of pulsed electric field-induced ROS burst in metabolite changes during potato processing: Integrated transcriptomic and metabolomic analysis - Renjie Zhao; Qiannan Liu; Jing Li; Run Shi; Ruixuan Zhao; Honghai Hu (Food Chemistry, 2026)

The oldest rock in the Eurasian continent was reworked from Hadean protocrust - Xiao-Fei Qiu; Da Wang; Xi-Run Tong; Shi-Wen Xie; Nian-Wen Wu; Fei Liu; Yu-Sheng Wan (Gondwana Research, 2026)

Gram-scale photocatalytic benzyl alcohol oxidation via photon-heteroatom jointly promoted redox cycling over nickel-based Pickering emulsion - Shihao Du; Run Shi; Gongao Peng; Jiaqi Zhao; Lingsong Wang; Feng Ryan Wang; Tierui Zhang (Science Bulletin, 2026)

CARE: a next-generation high resolution cloud and radiation remote sensing product and its Earth system applications - Husi Letu; Huazhe Shang; Run Ma; Chong Shi; Takashi Y. Nakajima; Hiroshi Ishimoto; Jérôme Riedi; Lesi Wei; Ri Xu; Dabin Ji; Qixiang Sun; Sude Bilige; et al. (Science Bulletin, 2026)

Biogas slurry substitution for chemical fertilizer under fertigation enhances soil fertility and maize yield sustainability: A meta-analysis - Yue Jiang; Bin Shi; Run Xue; Hong Li; Bingyu Li; Luya Wang; Nuo Li (Journal of Environmental Management, 2026)

The remediation effect of C/N cycling driven by the synergistic interactions of functional strains and straw in poly(butylene adipate-co-terephthalate)-contaminated soil - Hong Zhang; Lisha Song; Run Hu; Huan Liu; Yaohua Shi; Qiang Liu; Yanjiao Qi (Journal of Environmental Sciences, 2026)

Unveiling rock heterogeneity-driven multiphysics field coupling mechanisms under microwave radiation by 3D numerical study - Run Shi; Jian Zhao (Computers and Geotechnics, 2026)

Coordinated EISCAT and all-sky imager observations of dayside aurora effects on polar cap patch vertical properties - Zhiwei Wang; Desheng Han; Huixuan Qiu; Yong Wang; Huigen Yang; Jian Zhang; Jianjun Liu; Xiangcai Chen; Qiang Zhang; Su Zhou; Run Shi (Science China Earth Sciences, 2026)

Research progress on co-processing of MSWI FA using high-temperature industrial waste heat - Hongzhi Ma; Congqi Zhang; Hao Wang; Run Shi; Hao Li; Yan Zhang; Xuguang Wang; Wei Su; Yi Xing; Lei Zheng (Process Safety and Environmental Protection, 2026)

Observational evidence of ionospheric feedback effect in generating throat aurora - Huixuan Qiu; Desheng Han; Yong Wang; Qiang Zhang; Huiting Feng; Run Shi; Shunrong Zhang; Zhiwei Wang; Yongliang Zhang (Science China Earth Sciences, 2026)

Short-, medium-, and long-chain chlorinated paraffins in sediments from the Pearl River Delta, China: Occurrence, sources, and risks - Fei-Xiang Xie; Yu-Fang Huang; Yong-Hong Zhang; Ya-Hui Xue; Run-Lin Chen; Xiao-Mei Huang; Hong-De Shi; Jia-Hui Huang; Hui-Ru Li (Science of The Total Environment, 2026)

Alstoniaschines A‒I, nine undescribed alkaloids from Alstonia scholaris and their potential medicinal effects on diabetic nephropathy - Wen-Jie Sun; Shi-Shi Qin; Xian-Run Wu; Yun-Li Zhao; Xu-Jie Qin; Xiao-Dong Luo (Phytochemistry, 2026)

Effect of air frying, oven baking, pan frying, and deep frying on flavor profile and acrylamide formation in reheated hash browns - Run Shi; Qiqi Mi; Renjie Zhao; Qiannan Liu; Jing Li; Wei Liu; Ruixuan Zhao; Honghai Hu (Food Chemistry, 2026)

Oral Administrations of Short-Chain Fatty Acids or Probiotics Extend the Survival Times and Mitigate the Neuropathological Damages in the Scrapie-Infected Hamsters - Yuan Wang; Dong-Lin Liang; Run-Dong Cao; Ruhan A.; Jia-Feng Zeng; Bing Xu; Ju-Zheng Li; Wei-Wei Zhang; Li-Ping Gao; Kang Xiao; Xiao-Ping Dong; Qi Shi (Molecular Neurobiology, 2026)

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)

Dynamic exposure to urban lakefront spaces: Unveiling the role of social infrastructure in shaping visitation - Run Shi; Xiangbin Peng; Yuanzheng Cui; Xuejun Duan; Dong Xu; Lei Wang; Anthony Gar-On Yeh (Landscape and Urban Planning, 2025)

Soil cadmium and pyrene drive earthworm burrowing inhibition and modify mucus characteristics: Toward non-destructive biomarkers - Weipeng Wang; XiaoSa Wang; Run Su; Qian Xu; Congying Wang; Yonghua Zhao; Zhiming Shi (Journal of Hazardous Materials, 2025)

High-precision geochronology of the Early Cretaceous Jiufotang Formation: Temporal constraints on the late phase of the Jehol Biota - Yu-Ting Zhong; Magdalena H. Huyskens; Run-Jian Chu; Han-Qing Yang; Jian-Fang Hu; Ya-Qiong Wang; Shi-Xi Cai; Qiong Wu; Qiang Ma; Huai-Chun Wu; Qing-Zhu Yin; Yi-Gang Xu (Earth and Planetary Science Letters, 2025)

Elevated incubation temperature enhances the growth performance and increases the percentage of female offspring in the swimming crab, Portunus trituberculatus - Shurong Wu; Qingwei Chen; Ronghua Li; Run Tong; Chunlin Wang; Changkao Mu; Ce Shi; Weiwei Song (Aquaculture International, 2025)

Frititaipaines A−O, undescribed cevanine-type isosteroidal alkaloids from the bulbs of Fritillaria taipaiensis and their anti-neuroinflammatory and AChE inhibitory activities - Zai-Long Huang; En-Ke Qu; Lan-Run Yang; Rui Luo; Yan-Ni Liang; Shi-Jun Liu; Yuan-Zhen Xu; Dong-Bo Zhang (Phytochemistry, 2025)

An ascorbic acid responsive nanoprobe for food shelf-life determination and plant growth assessment - Dihua Tian; Zexi Zhang; Suzanne Mathews Plavilathundil; Xinyang Tian; Maral Seididamyeh; Mazen Alanazi; Anh Phan; Miaomiao Wu; Jiahua Shi; Yasmina Sultanbawa; Bernard J. Carroll; Run Zhang (Food Chemistry, 2025)

The degradation of polyethylene by soil microbial communities was significantly enhanced through the Fe³ ⁺-induced Fenton-like reaction - Run Hu; Lisha Song; Huan Liu; Huaxian Tao; Yaohua Shi; Qiang Liu; Hong Zhang; Yanjiao Qi (Process Safety and Environmental Protection, 2025)

Naked mole-rat-derived high molecular weight hyaluronic acid protects against DSS-induced intestinal inflammation - Shuyin Wu; Lei Xing; Xiaolong Wu; Run Quan; Keyi Du; Jianchun Han; Huili Tong; Shuai Shi (Food Bioscience, 2025)

Social areas revisited through the lens of mobility: A comparative study of the traditional and mobility approaches - Run Shi; Anthony Gar-On Yeh; Fang Bian (Computers, Environment and Urban Systems, 2025)

Divergent effects of cropland management practices and global change factors on microbial necromass across ecosystems: implications for soil organic carbon - Chen-Hao Lyu; Wen-Jun He; Peng Chen; Xin-Xin Jing; Guo-Shi Zhang; Run-Qin Zhang; Zi-Yan Li; Zhi-Guo Li; Yi Liu (CATENA, 2025)

Proteomic Composition of Acute Ischemic Stroke Thrombi Retrieved via Endovascular Thrombectomy Is Associated with Stroke Etiology - Run-Hao Jiang; Xing-Long Liu; Xiao-Quan Xu; Hai-Bin Shi; Sheng Liu (Translational Stroke Research, 2025)

Urban-industrial synergies in Sustainability: Evaluating the Co-processing of MSWI fly ash in industrial kilns from environmental and economic perspectives - Run Shi; Fan Fei; Xuguang Wang; Dawei Liu; Shuang Wu; Junwei Bai; Yan Zhang; Wei Su; Rongrong Lei; Hao Wang; Hongzhi Ma (Journal of Cleaner Production, 2025)

Geochemistry characteristics and tectonic significance of the ‘ “mafic” S-type granites’ - Qiang Shi; Xiang-Zhi Chen; Run-Xiao Shu; Yu-Song Chen; Shi-Jie Wang; Zhong-Yuan Xu; Kai-Yun Chen; Guo-Chun Zhao (International Geology Review, 2025)

Impact of collagen degradation on the textural quality of salmon (Salmo salar): A preliminary study from the perspective of endogenous collagenase and bacteria - Lu Sun; Run-Jian Gao; Cheng-Jian Shi; Andrew M. Hemmings; Yun-Fang Qian (Food Bioscience, 2025)

Effects of periodic starvation on the characteristics and microbial communities of anammox sludge - Yufeng Zheng; Liangliang Shi; Run Su; Wenhui Min; Yan Wei; Bin Ma (Journal of Environmental Chemical Engineering, 2025)

Rational metabolic engineering of Escherichia coli for the industrial-scale production of l-phenylalanine - Minliang Chen; Chao Han; Peng Zhou; Run Shi; Zhiwei Xing; Qianqian Chen; Gou-an Xie; Rufei Xie; Wei Tan; Hengyu Liang (Bioresource Technology, 2025)

Comammox and AOA responses to ammonia loading rate in oligotrophic environments - Run Su; Litong Shi; Yan Wei; Bin Ma (Water Research, 2025)

Enhancing fruit quality through unraveling the molecular and physiological basis and preventing cracking in jujube (Ziziphus jujuba Mill.) - Hong-Xiang Zhou; Run-Zhe Wang; Wen-Ting Luo; Yang Liang; Shi-Yu Liu; Juan Chen; Ji-Qing Peng; Yan-Xia Fan; Shu-Zhan Li; Chuan Guo; Zi-Qiang Zhang; Feng-Xia Shao; et al. (Postharvest Biology and Technology, 2025)

Characterization of β-cyclodextrin inclusion complexes embedded with lemongrass and basil essential oils and their modified sustained-release pads for large yellow croaker (Larimichthys crocea) fillet preservation - Yun-Fang Qian; Cheng-Jian Shi; Lu Sun; Run-Jian Gao; Sheng-Ping Yang (Food Bioscience, 2025)

Remote sensing of liquid cloud profiles based on an analytical cloud profiling model - Huazhe Shang; Husi Letu; Lesi Wei; Run Ma; Yutong Wang; Zhaoxin Cai; Shuai Yin; Chong Shi (Science China Earth Sciences, 2025)

Development of a hybrid algorithm for the simultaneous retrieval of aerosol optical thickness and fine-mode fraction from multispectral satellite observation combining radiative transfer and transfer learning approaches - Chenqian Tang; Chong Shi; Husi Letu; Shuai Yin; Teruyuki Nakajima; Miho Sekiguchi; Jian Xu; Mengjie Zhao; Run Ma; Wenwu Wang (Remote Sensing of Environment, 2025)

Understanding the impact of promoters on enhancing and inhibiting the sulphur resistance and regeneration of supported Pd catalysts for complete methane oxidation - Abubakar Yusuf; Yong Ren; Yun Liu; Li Shi; Zhiyu Xiao; Run Pan; Zheng Wang; Hainam Do; Jianrong Li; Jun He (Chemical Engineering Journal, 2025)

Paleoproterozoic granite in the Khondalite Belt, northern margin of the North China Craton: Response to the assembly of the Columbia supercontinent - Qiang Shi; Run-Xiao Shu; Xiang-Zhi Chen; Guo-Chun Zhao; Yu-Song Chen; Zhao-Sheng Wang; Long Ma; Zhong-Yuan Xu; Zheng-Hong Liu; Kai-Yun Chen; Hui-Chu Wang (Precambrian Research, 2025)

Cadmium and pyrene in the soil modify the properties of earthworm-mediated soil - Zhiming Shi; Jie Yan; Run Su; Shuyu Shi; Wenwen Li; Yonghua Zhao; Juan Zhang; Congying Wang (Science of The Total Environment, 2024)

Effect of Voluntary Wheel Running on Anxiety- and Depression-Like Behaviors in Fluoride-Exposed Mice - Mengjie Qi; Yue Wu; Han Shi; Jie Liu; Run Zhu; Jixiang Wang; Amna Rafique; Bo Yang; Ruiyan Niu; Ding Zhang; Zilong Sun (Biological Trace Element Research, 2024)

High permeability Performance TFC Nanofiltration Membrane with Two dimensional Nanochannels Support Layer Fabricated by Dissolving of Nanosheets - Run-Hua Tang; Shu-Jun Deng; Sheng-Nan Zhao; Yong Shi; Jing Ye; Gui-E Chen; Zhen-Liang Xu (Journal of Environmental Chemical Engineering, 2024)

Aerobic granular sludge for swine wastewater treatment: Implications for antibiotic and antibiotic resistance gene elimination - Meng-Yuan Li; Run-Dong Zhang; Shuang-Shuang Liu; Cheng-Lei Pei; Liang-Ying He; Jian-Liang Zhao; You-Sheng Liu; Yi-Jing Shi; Guang-Guo Ying (Bioresource Technology, 2024)

Metagenomic investigation of antibiotic resistance genes and resistant bacteria contamination in pharmaceutical plant sites in China - Run-Dong Zhang; Fang-Zhou Gao; Yi-Jing Shi; Jian-Liang Zhao; You-Sheng Liu; Liang-Ying He; Guang-Guo Ying (Environmental Pollution, 2024)

A temporal gap filling approach for GNSS-IR soil moisture inversion based on generalized extension - Haodong Zhao; Junna Shang; Fangzhou Li; Huli Shi; Run Pang (Advances in Space Research, 2024)

PLTS/ARAS-based financing risk resilience capability evaluation for fisheries enterprise: A case study of green transformation and upgrading - Shi-Tong Zhang; Miao-Miao Jiang; Hong-Run Chu (Journal of Environmental Management, 2024)

Occurrence and mechanism of sulfamethoxazole in alginate-like extracellular polymers from excess sludge - Chen Shi; Ming Cheng; Run-Gen Zeng; Cong-Cong Li; Qian Wang; Li-Ting Hao; Ran-Bin Liu; Xiao-Di Hao; Xiang-Yang Wang; Yuan-Yuan Wu (Bioresource Technology, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Preparing a heavy-metal adsorbent based on alginate-like extracellular polymers from conventional activated sludge via polyethyleneimine grafting - Chen Shi; Run-Gen Zeng; Shi-Chao Yuan; Lin Zhang; Xiang-Yang Wang; Li-Ting Hao; Xiao-Di Hao; Nan Zhang; Yuan-Yuan Wu (Sustainable Chemistry and Pharmacy, 2024)

Indole-3-acetic acid improves periphyton's resistance to ultraviolet-B: From physiological-biochemical properties and bacteria community to livestock-polluted water purification - Tianyu Shi; Maobulin Lure; Run Zhang; Zhiheng Liu; Qianming Hu; Jia Liu; Shengtao Yang; Liandong Jing (Environmental Research, 2024)

Macroporous polyvinyl alcohol-formaldehyde-silicon composite sponges with designed structure for high-efficiency water-in-oil emulsion separation - Di Sha; Run Zheng; Kai Shi; Baolong Wang; Yanxiong Pan; Xiangling Ji (Journal of Environmental Chemical Engineering, 2024)

A review of alginate-like extracellular polymers from excess sludge: Extraction, characterization, and potential application - Run-Gen Zeng; Chen Shi; Li-Ting Hao; Ao Huang; Tian Yuan; Nan Zhang (Journal of Water Process Engineering, 2023)

Comparative study on ventilation and air conditioning system schemes based on virus pollution control in hospital infusion room - Weixue Cao; Xudong Zhang; Wanxiang Yao; Run Sun; Yutong Du; Quanbin Shi; Zipeng Li (Aerobiologia, 2023)

Study on liquid dispersion characteristics in trickle bed reactor based on image processing - Run Guo; Bin Wei; Huanzhi Liu; Xiaogang Shi; Xingying Lan; Jinsen Gao (Fuel, 2023)

Methyl-functionalized Zn-MOF for selective adsorption and separation of acetylene - Zi-Han Wang; Run-Han Su; Gang-Ding Wang; Wen-Juan Shi; Lei Hou (Journal of Environmental Chemical Engineering, 2023)

Characterization of a gE/gI/TK gene-deleted pseudorabies virus variant expressing the Cap protein of porcine circovirus type 2d - Rui-Qin Xu; Lin-Qing Wang; Hui-Hua Zheng; Run-Bo Tian; Lan-Lan Zheng; Shi-Jie Ma; Hong-Ying Chen (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Manual correction of genome annotation improved alternative splicing identification of Artemisia annua - Zhaoyu Liu; Yupeng Du; Zhihao Sun; Bohan Cheng; Zenghao Bi; Zhicheng Yao; Yuting Liang; Huiling Zhang; Run Yao; Shen Kang; Yuhua Shi; Huihua Wan; et al. (Planta, 2023)

Evaluation and uncertainty analysis of Himawari-8 hourly aerosol product version 3.1 and its influence on surface solar radiation before and during the COVID-19 outbreak - Chenqian Tang; Chong Shi; Husi Letu; Run Ma; Mayumi Yoshida; Maki Kikuchi; Jian Xu; Nan Li; Mengjie Zhao; Liangfu Chen; Guangyu Shi (Science of The Total Environment, 2023)

Suppression effects and mechanisms of three typical solid suppressants on titanium hydride dust explosions - Shi-zhou Li; Yang-fan Cheng; Rui Wang; Meng Li; Run Li; Hong-hao Ma (Process Safety and Environmental Protection, 2023)

Lateral bearing capacity and calculation method of pile-bucket foundation in clay for offshore wind turbines - Run Liu; Jieyang Shi; Guangsi Chen; Xu Yang (Ocean Engineering, 2023)

Association between nitrogen dioxide concentration and hypertension hospitalization: A multicenter time-series analysis in Xinxiang, China - Shi-qi Ge; Yong-bin Wang; Fei Lin; Run-ran Miao; Kai Zhang; Li Li; Hui-ge Guo; Qian Wang; Li Zhang; Zhi-gang Chen; Guo-an Zhao (Atmospheric Pollution Research, 2023)

Retrieval of cloud microphysical properties from Himawari-8/AHI infrared channels and its application in surface shortwave downward radiation estimation in the sun glint region - Gegen Tana; Xu Ri; Chong Shi; Run Ma; Husi Letu; Jian Xu; Jiancheng Shi (Remote Sensing of Environment, 2023)

Extracting compositional blocks of alginate-like extracellular polymers (ALE) from conventional activated sludge (CAS) - Chen Shi; Run-Gen Zeng; Li-Ting Hao; Xiao-Di Hao; Ji Li (Science of The Total Environment, 2023)

Metabolomics and lipidomics profiles related to intramuscular fat content and flavor precursors between Laiwu and Yorkshire pigs - Xinhua Hou; Run Zhang; Man Yang; Naiqi Niu; Junchao Wu; Ze Shu; Pengfei Zhang; Lijun Shi; Fuping Zhao; Ligang Wang; Lixian Wang; Longchao Zhang (Food Chemistry, 2023)

Biotransformation of sulfamonomethoxine in a granular sludge system: Pathways and mechanisms - Meng-Yuan Li; Run-Dong Zhang; Yi-Xing Lin; Qi-Wen Li; Qiu-Yue Zhao; Zong-Xi Zhao; Zhong-Ming Ling; Long-Fei Shu; Min Zhang; Li-Xin Hu; Yi-Jing Shi; Guang-Guo Ying (Chemosphere, 2023)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

High-precision downward continuation of potential fields algorithm utilizing adaptive damping coefficient of generalized minimal residuals - Zhi-Hou Zhang; Xiao-Long Liao; Ze-Yu Shi; Anthony R. Lowry; Yu Yao; Run-Qi Lu; Xiang-Tai Fan; Peng-Fei Liu; Si-Wei Zhao (Applied Geophysics, 2020)

Immune landscape and a novel immunotherapy-related gene signature associated with clinical outcome in early-stage lung adenocarcinoma - Xuanwen Bao; Run Shi; Tianyu Zhao; Yanfang Wang (Journal of Molecular Medicine, 2020)
Patients with early-stage lung adenocarcinoma (LUAD) exhibit different overall survival (OS) rates and immunotherapy responses. Understanding the immune landscape facilitates the personalized treatment of LUAD. The immune cell populations in tumour tissues were quantified to depict the immune landscape in early-stage LUAD patients in The Cancer Genome Atlas (TCGA). Early-stage LUAD patients in three immune clusters identified by the immune landscape exhibited different survival potentials. A prognostic immune-related gene signature was built to predict the survival of early-stage LUAD patients. Several machine learning methods (support vector machine, naive Bayes, random forest, and neural network-based deep learning) were applied to train the classifiers to identify the immune clusters in early-stage LUAD based on the gene signature. The four classifiers exhibited a robust effect in identifying the immune clusters. A random forest regression model identified that TP53 was the most important gene mutation associated with the immune-related signature. Furthermore, a decision tree and a nomogram were constructed based on the immune-related gene signature and clinicopathological traits to improve risk stratification and quantify risk assessment for individual patients. Five external test cohorts were applied to validate the accuracy of the immune-related signature. Our study might contribute to the development of immunotherapy and the personalized treatment of early-stage LUAD. Key messages Immune landscape correlates with the clinical outcome of early-stage adenocarcinoma (LUAD). Machine learning methods identifies a prognostic gene signature to predict the survival and prognosis of early-stage LUAD. TP53 gene mutation status correlates with the immune landscape in early-stage LUAD.

Development of a membrane lipid metabolism–based signature to predict overall survival for personalized medicine in ccRCC patients - Maode Bao; Run Shi; Kai Zhang; Yanbo Zhao; Yanfang Wang; Xuanwen Bao (EPMA Journal, 2019)

DNMT3A controls miR-200b in cardiac fibroblast autophagy and cardiac fibrosis - Xu-Dong Zhao; Run-He Qin; Jing-Jing Yang; Sheng-Song Xu; Hui Tao; Xuan-Sheng Ding; Kai-Hu Shi (Inflammation Research, 2018)

Evaluation of the possible slip surface of a highly heterogeneous rock slope using dynamic reduction method - Guo-qing Chen; Run-qiu Huang; Feng-shou Zhang; Zhen-fei Zhu; Yu-chuan Shi; Jian-chao Wang (Journal of Mountain Science, 2018)

Increasing the yield of middle silk gland expression system through transgenic knock-down of endogenous sericin-1 - Sanyuan Ma; Xiaojuan Xia; Yufeng Li; Le Sun; Yue Liu; Yuanyuan Liu; Xiaogang Wang; Run Shi; Jiasong Chang; Ping Zhao; Qingyou Xia (Molecular Genetics and Genomics, 2017)

Phytochemicals and biological activities of Artemisia sieversiana - Shi-Jun Liu; Zhi-Xin Liao; Zhi-Shu Tang; Chun-Li Cui; Hong-Bo Liu; Yan-Ni Liang; Yu Zhang; Huan-Xian Shi; Yao-Run Liu (Phytochemistry Reviews, 2017)

High-order generalized screen propagator migration based on particle swarm optimization - Run He; Jia-Chun You; Bin Liu; Yan-Chun Wang; Shi-Guang Deng; Feng-Qi Zhang (Applied Geophysics, 2017)

Silencing of HMGA2 promotes apoptosis and inhibits migration and invasion of prostate cancer cells - Zhan Shi; Ding Wu; Run Tang; Xiang Li; Renfu Chen; Song Xue; Chengjing Zhang; Xiaoqing Sun (Journal of Biosciences, 2016)

Spatial differentiation of tourism impact based on the perception of residents in mountainous valley resorts - Shan-shi Li; Jia-ming Liu; Run Wang; He Zhu (Journal of Mountain Science, 2014)

Isolation and Structural Characterization of Lignin Polymer from Dendrocalamus sinicus - Zheng-Jun Shi; Ling-Ping Xiao; Jia Deng; Run-Cang Sun (BioEnergy Research, 2013)

Biodegradation of Lignocellulose by White-Rot Fungi: Structural Characterization of Water-Soluble Hemicelluloses - Ling-Ping Xiao; Zheng-Jun Shi; Yuan-Yuan Bai; Wei Wang; Xue-Ming Zhang; Run-Cang Sun (BioEnergy Research, 2013)

Characterization of Lignins Isolated with Alkaline Ethanol from the Hydrothermal Pretreated Tamarix ramosissima - Ling-Ping Xiao; Zheng-Jun Shi; Feng Xu; Run-Cang Sun (BioEnergy Research, 2013)

Selective pressure dominates the synonymous codon usage in parvoviridae - Sheng-Lin Shi; Yi-Ren Jiang; Yan-Qun Liu; Run-Xi Xia; Li Qin (Virus Genes, 2013)

XRCC1 Arg399Gln and clinical outcome of platinum-based treatment for advanced non-small cell lung cancer: a meta-analysis in 17 studies - Jian Chen; Qing-wei Zhao; Gen-ming Shi; Lin-run Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Effect of Different Levels of Copper and Molybdenum Supplements on Serum Lipid Profiles and Antioxidant Status in Cashmere Goats - Wei Zhang; Yu Zhang; Shi W. Zhang; Xian Z. Song; Zhi H. Jia; Run L. Wang (Biological Trace Element Research, 2012)

A minimum traveltime ray tracing global algorithm on a triangular net for propagating plane waves - Shi-Jian Yu; Run-Ze Liu; Jiu-Long Cheng (Applied Geophysics, 2010)

Two new coumarins from Edgeworthia chrysantha - Xiao-Jia Hu; Hui-Zi Jin; Wei-Dong Zhang; Wei Zhang; Shi-Kai Yan; Run-Hui Liu; Yun-Heng Shen; Wen-Zheng Xu (Natural Product Research, 2009)

Effects of exogenous putrescine on gas-exchange characteristics and chlorophyll fluorescence of NaCl-stressed cucumber seedlings - Run Hua Zhang; Jun Li; Shi Rong Guo; Takafumi Tezuka (Photosynthesis Research, 2009)

Molecular interaction between prion protein and GFAP both in native and recombinant forms in vitro - Chen-Fang Dong; Xiao-Fan Wang; Xin Wang; Song Shi; Gui-Rong Wang; Bing Shan; Run An; Xiao-Li Li; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2008)

Different expression patterns of CK2 subunits in the brains of experimental animals and patients with transmissible spongiform encephalopathies - Jian-Ming Chen; Chen Gao; Qi Shi; Bing Shan; Yan-Jun Lei; Chen-Fang Dong; Run An; Gui-Rong Wang; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Archives of Virology, 2008)

Physical geographical background of the culture of traditional Chinese residential architecture - Run Sha; Gaojun Shi; Shaoying Chu (Chinese Geographical Science, 1999)